2007
DOI: 10.1007/s00105-007-1382-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimierung der dermatopathologischen Diagnostik durch digitale Fotografie und Internet

Abstract: Clinicopathologic correlation is the basis of a precise diagnosis. Especially in dermatopathology, the precision of a microscopic diagnosis may significantly be increased by thorough knowledge of the clinical picture. The advent of digital photography, the internet and moderately priced CDs and USB-sticks have made it possible to establish and maintain a time-saving, low-cost picture data transfer between dermatologist and dermatopathologist which is optimally suited for clinicopathologic correlation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 20 publications
0
7
0
3
Order By: Relevance
“…The need for appropriate clinical correlation and clinical images has already been underlined. 8,9 Recently, the usefulness of clinicopathologic correlation for the histopathologic diagnosis of melanocytic skin tumor was demonstrated, 3,6 and it was suggested that all biopsy specimens of clinically difficult pigmented lesions should be assessed histopathologically with knowledge of the clinical picture. 10 In this context, we stress that dermatopathology is macroscopic and microscopic pathology of the skin, and that evaluation of clinical presentation (macroscopy) represents a crucial step in the diagnostic process.…”
Section: Discussionmentioning
confidence: 99%
“…The need for appropriate clinical correlation and clinical images has already been underlined. 8,9 Recently, the usefulness of clinicopathologic correlation for the histopathologic diagnosis of melanocytic skin tumor was demonstrated, 3,6 and it was suggested that all biopsy specimens of clinically difficult pigmented lesions should be assessed histopathologically with knowledge of the clinical picture. 10 In this context, we stress that dermatopathology is macroscopic and microscopic pathology of the skin, and that evaluation of clinical presentation (macroscopy) represents a crucial step in the diagnostic process.…”
Section: Discussionmentioning
confidence: 99%
“…Now, digital photography is available and the pathologist can reach to this data whenever it is needed. 15 In a study performed on 100 consecutive skin biopsies in which an inflammatory dermatosis was queried, the rates of accurate diagnoses were 53% in cases which were history blind and 78% in cases in which clinical information was available. 31 In another study which compared the results of the biopsies taken by dermatologists and nondermatologists, it was found that inflammatory skin diseases were correctly diagnosed in 71% of the cases by dermatologists but in only 34% of the cases by nondermatologists emphasizing that the histopathological diagnosis will be limited or restricted without sufficient clinical data.…”
Section: Clinicopathologic Correlationmentioning
confidence: 99%
“…But their frequencies differ from those in adults. [13][14][15] Also, skin diseases in children are not necessarily smaller versions of those that develop in adults. There are some conditions, in fact, that are virtually confined to the pediatric age group.…”
mentioning
confidence: 99%
“…Sin embargo, su frecuencia difiere de la de los adultos. [13][14][15] Asimismo, las dermopatías en niños no constituyen necesariamente versiones más pequeñas de las que se presentan en los adultos. De hecho, algunas enfermedades están virtualmente limitadas al grupo etario pediátrico.…”
Section: Dermatología Pediátricaunclassified